Justification Not by Faith Alone: Clergy Generating Trust and Certainty by Revealing Thought - Djupe, Paul A. (Politics and religion, 2009)
While our intuition is that religious elites influence the political behavior of their audiences, just how that influence takes place is essentially unknown. Among many possible mechanisms, we investigate a new one: the effects of the decision-making process information that is included in elite statements. We believe that "process cues" paralleling those preferred by respondents bolster trust in the source and augment the ability to form determined attitudes. We test this proposition in the context of a survey experiment that focuses on environmental racism. We present competing arguments provided by a reverend and a professor, variably assigning the arguments and presence of elite process cues. We find that process cues do affect trust and attitudinal ambivalence, but in ways that challenge some pervasive assumptions about the integrity and importance of religious groups in politics.